The status and rights of women mentioned in Islam - Zaw, Cho Cho; Min @ Mohd Omar, Myat (International Journal for Studies on Children, Women, Elderly and Disabled People (IJCWED), 2017)
Women rights movement is not new to this era; it is a series of events that has been taken place in different parts of the world throughout the centuries. With the advancement of society, the discrimination against women has been reduced to a certain degree, but the violations of their rights are still observed in some countries. They are still seen as being the victims of hinder access to quality education, health care services, and occupation. On the other hand, a great burden has been seen among women in the so-called equal rights society. They are taking more than one role, the role of the bread winner in addition to their primary role of being the wife, mother, and daughter of the family. Furthermore, regarding treatment of women is one of the misunderstood issues about Islam which might be the fact that some media portrayed the negative image of Islam. It could also be partly due to our fellow Muslims’ treatment towards women. Thus, this study aims to explore more about the rights of women, their roles, status, and responsibilities as stipulated by Islam. Since this paper is based on the non-empirical, literature based study, the revealed knowledge; Quran and the Sunnah are taken as the main source of discussions on the topics of women rights in Islam, and further added the knowledge of scholars in the related area. And the Islamic literature points out that there is no discrimination against women in Islam. Men and women are being created equal in the spiritual sense. Intelligence, education and knowledge of women are no inferior to those of men. Though, women are excused from performing certain responsibilities based on their nature, and biological build up, women have extra advantages in terms of economic rights. They have freedom of choices as men do regarding their carrier, marriage, and even divorce if it is with the valid reason. It is hoped that this paper helps to increase awareness, claim back their rights as women, prevent violence against women, and reduce misunderstanding about Islam.